Inclusion of students with ASD in regular education and contributions of the Individualized Educational Plan: a systematic literature review (Olhar de Professor, 2023)
Based on the theme inclusion of students with autism in regular education and contributions of individualized educational plan, this article aims to search in the literature for relationships among school inclusion, individualized educational plan (IEP) and development of skills and abilities of students with autism spectrum disorder (ASD) in regular education. It is believed that the child with ASD has the right to build learning and not just be inserted into the classroom without an appropriate pedagogical planning that considers his abilities, difficulties and needs. To identify findings of studies already conducted on this topic, an integrative literature review was conducted in the Scielo and Google Academic databases. The investigation revealed that regular schools still need curricular adaptations for inclusion to actually happen. Frente a essa discussão, evidenciou-se a importância do uso do PEI para o processo de inclusão na escola regular.
Keywords: School inclusion.; Individualized Educational Plan; Autism Spectrum Disorder